Evaluation of a maternal health care project in South West Shoa Zone, Ethiopia: before-and-after comparison. Issue 1 (December 2016) - Wilunda, Calistus; Tanaka, Shiro; Putoto, Giovanni; Tsegaye, Ademe; Kawakami, Koji
Abstract Background Despite recent achievements in health targets, Ethiopia still faces challenges in health service delivery. Between 2012 and 2015, a non-governmental organisation (NGO), Doctors with Africa CUAMM, implemented a multifaceted project aimed at improving access to maternal and child health services in three districts in Ethiopia. This paper evaluates the performance of this project, based on four maternal health indicators. Methods A before-and-after study utilising data collected through cross-sectional surveys involving 999 women was conducted. The date of delivery was used to stratify the intervention period as follows: pre-intervention, early intervention, and late intervention. Changes during the intervention in the coverage of four antenatal care (ANC) visits, receipt of three basic components of ANC, skilled birth attendant (SBA) at delivery, and postnatal care (PNC) in seven days were assessed using logistic regression, adjusting for socio-demographic factors. Results There was an increase in the coverage of receipt of all three ANC components and SBA at delivery between the pre-intervention period and the late intervention period. The percent of health centre deliveries increased from 7.3 % in the pre-intervention period to 35.6 % in the late intervention period. The odds of receiving all three components of ANC were twice higher in the late intervention period than in the pre-intervention period (OR 2.09; 95 % CI 1.12–3.89). The odds of SBA at delivery were five times higher in the late intervention period than in the pre-intervention period (OR 5.04; 95 % CI 2.53–10.06). There was no significant change in the coverage of four ANC visits and PNC after accounting for sociodemographic factors. Conclusions This NGO implemented maternal health project in three districts in Ethiopia was associated with increased likelihood that a pregnant woman would receive three basic components of ANC and be assisted by a SBA at delivery. Increase in skilled birth attendance was driven by increased utilisation of health centres. More efforts are needed to bolster the coverage of ANC and PNC.